DIAGNOSIS OF ENDOCRINE DISEASE: Pituitary stalk interruption syndrome: etiology and clinical manifestations. Issue 5 (November 2019) - Vergier, Julia; Castinetti, Frederic; Saveanu, Alexandru; Girard, Nadine; Brue, Thierry; Reynaud, Rachel
Abstract : Pituitary stalk interruption syndrome (PSIS) is a congenital pituitary anatomical defect. This syndrome is an antenatal developmental defect belonging to the holoprosencephaly phenotype spectrum. It is heterogeneous regarding clinical, biological and radiological presentation and is characterized by the following triad: thin (<1 mm) or interrupted pituitary stalk connecting the hypothalamus to the pituitary gland, no eutopic posterior lobe, and hypoplasia or aplasia of the anterior lobe. This review reports current knowledge about the composite pathogenesis, for which underlying mechanisms remain unclear. Current data suggest genetic origins involving early developmental gene mutations with complex inheritance patterns and environmental influence, placing PSIS at the crossroads between Mendelian and multifactorial diseases. The phenotype associated with PSIS is highly heterogeneous with a high incidence of various combinations of hormonal deficiencies, sometimes associated with extra-pituitary birth defects. The age at onset is variable, but typical presentation is evolutive combined anterior pituitary hormone deficiencies at pediatric age, which progress even during adulthood to panhypopituitarism. Therefore, patients' follow-up throughout life is essential for adequate management.